Hiring decision of agricultural mechanization services by rice farmers in the Alnajaf Province of Iraq - Kadhim, Zuhal Rdhaiwi (2018)
The use of machinery in different agricultural production processes has led to the occurrence of latent changes in agriculture like quantity increase and quality of farm products, decrease of farm production costs and increase of cultivated areas, and the degree of technological progress of any country usually depends on the extent of mechanization that is used in this country. However, investments in ownership of agricultural machinery services and access to them, especially for small-scale farmers, may not be the minimum cost option in comparison with hiring these required services through oral or written agricultural contracts. The major principle to select the optimal decision for obtaining agricultural machinery services, at small-scale farmers level, includes the analysis of the transaction costs when machinery services are hired and estimating both the fixed and variable costs of owning these services. The main aim of this research is to analyze the hiring decision of agricultural mechanization services by rice farmers in Alnajaf Province. And specifically, the objectives are: 1) to clarify respondents’ socio-economic characteristics in relation to the hiring decision of agricultural machinery services; 2) to determine the core attributes of transaction costs which may affect or encourage respondents’ decisions to hire agricultural mechanization services; 3) to estimate the relationship between the affecting variables and respondents’ decisions to hire agricultural mechanization services; and 4) to test whether the hiring decision of agricultural machinery services is better for study sample in comparison with the other potential alternatives. The theoretical framework based on two economic approaches of analysis of hiring decision odds: 1) developed on the basis of transaction cost economics model, adapted and interpreted in the thesis to deal with the context of the study; and 2) included the financial approach of engineering costs analysis of agricultural machineries services. The data were collected by simple random sampling method using a standardized questionnaire with open-ended and close-ended questions. Copies of the questionnaire were distributed to 391 respondents from among the rice farmers in Alnajaf Province. The study was carried out over a period of three months from April 2016 until end June 2016. Descriptive statistics, Likert scale, a qualitative response regression models and engineering costs analysis of agricultural machineries were used to analyze the respondents’ behaviors and decisions towards a hiring decision. The dependent variable in this study was derived from the question pertaining to ownership (own, hire, or other) of the agricultural machinery services used on the farm, while the independent variables include the key attributes of transaction costs theory and selected socio-economic characteristics of respondents. Results indicated that most of the respondents in the study region agree that monitoring and negotiation costs are important elements in hiring decision make process, as well as some transaction cost attributes such as a machine specificity, behavior uncertainty, frequency and measurability of the machinery services concerned are important in determining the hiring decision. The results also showed significant differences in hiring decision in relation to some socio-economic characteristics such as respondents’ age, farm area, the desire to use agricultural mechanization and education level. In addition, results of financial analysis of components of costs of hired agricultural machinery (tractors, farm sprayers and combine harvesters) pointed out that the investments on all new and used agricultural machinery in the study area are unprofitable based on pointers of breakeven point, net present value and benefit cost ratio. The study illustrates the benefits of transaction cost economics to better understand how and why respondents prefer to hire machinery services purchase their own equipment. In light of these results, the study determines that it is necessary and profitable for small scale farmers in Alnajaf Province to continue hiring various agricultural machinery services rather than purchase them. The study recommends that the policy of the Iraqi government should be more encouraging to markets of agricultural machinery services so as to minimize the transaction costs of trading the agricultural machinery services between tenant farmers and other contracting parties. As such, programmes of agricultural extension and farm support would be helpful in the development of small scale farmers. Iraqi government also should take responsibilities for distributing the machinery and providing credit amenities on supported rates to those farmers who are want to buy the machinery individually.